AN ANALYSIS OF THE INDONESIAN SHARIA BANKING DEVELOPMENT ROADMAP 2020-2025 - Hasan, Zulfikar (Online Journal of Islamic Management and Finance (OJIMF), 2023)
This article aims to examine the Roadmap that has been published by the Financial Services Authority (OJK) for the expansion of Islamic banking in Indonesia in the next five years. In particular, it seeks to analyze the main pillars that the Roadmap has identified to further the progress of Islamic banking in Indonesia. These pillars are strengthening the identity of Islamic banking, synergizing the Islamic economic ecosystem, and strengthening licensing, regulation, and supervision. This study applies a qualitative method to analyze the implementation of the 2020-2025 Islamic banking development roadmap. The data was analyzed using taxonomic analysis techniques method, that conducts not only a general exploration but also focuses on a particular domain in accordance with the research focus of the researcher. Because this research is qualitative in nature, the data was interpreted based on the content review system. The paper finds that the use of technology is one of the most important tools to achieve the three pillars of Islamic banking in Indonesia. Having the full support of all Islamic banking stakeholders is also another important factor that will further progress the industry. The analysis of the Islamic banking Roadmap provides an overview on the key pillars that have been identified as drivers for the future of Islamic banking in Indonesia. This will provide important knowledge to industry players, the academic and other stakeholder to understand the direction that the industry will be taking in the next five years so that they can collaborate effectively to support the progress of the industry. The analysis of the 2020-2025 Islamic banking development roadmap is a first in the existing literature. A critical analysis of this recently released document by the OJK in 2021 is deemed important to elucidate the future direction of the Islamic banking industry to stakeholders in Indonesia.